Valoración de riesgos mecánicos y seguridad laboral en el proceso de perforación de pozos en los taladros de la empresa petrolera Pdvsa servicios ecuador. Propuesta caracterización de riesgos y desarrollo de la matriz de factores de riesgos mecánicos por puestos de trabajo. - Herrera Terán, Hugo Fabián (2017)
PDVSA Servicios Ecuador is a company dedicated to drilling its activities involve mechanical risk factors that are addressed by the Industrial Safety it responsible to prevent accidents. A risk is the probability of happening of an event that can cause damage to a person's health and production processes. Accidents at work with machines related with Drilling can generally be by contact or to be stuck hith moving parts, to hit with some machine element or objets during the operation, as wellas crushing, shearing, cutting or sectioning, drag, impact, performance, friction or abrasion and material projection. In any production process that involvi the use of machinery can generate personnet riks, so it is vital to eliminate the probability of occurrence sa that we can ensure the health and integrity of the PDVSA Servicios Ecuador, staff. At firs this research hants to identify types of mechanical risks with higher probability of occurrence of accidents, in high risk activities of drilling processes and thus determine the existing risk factors, and from this result to perform the corresponding evaluation, to define the general recommendations of control measures these can be .- Elimination of risk, process, equipment and administrative substition, mechanical controls and the use of protective equipment in order to eliminate labor accidents caused by substandard conditions front mechanical risks. 513 CD resolution third attachment at IESS highlights the risk factors which are determined from a reactive perspective, that doesn't match with the present investigation, since the purpose of this is to form a proactive perspective so that these risks may not occur. For that reason we applied evaluation methods that permit to measure and evaluate those that are dangerous, to act as a priority and avoid those damages become real.